FirnCover visualization scripts - Vandecrux, Baptiste; MacFerrin, Michael J.; C. Max Stevens (Zenodo, 2022)
This repository contains Python scripts for vizualizing the FirnCoVer dataset. The dataset is available at: MacFerrin, M., Stevens, C. M., Vandecrux, B.: The Greenland Firn Compaction Verification and Reconnaissance (FirnCover) Dataset, 2013-2019. Arctic Data Center, https://www.doi.org/10.18739/A25X25D7M, 2021. and is described in: MacFerrin, M. J., Stevens, C. M., Vandecrux, B., Waddington, E. D., and Abdalati, W.: The Greenland Firn Compaction Verification and Reconnaissance (FirnCover) Dataset, 2013–2019, Earth Syst. Sci. Data Discuss. [preprint], https://doi.org/10.5194/essd-2021-274, in review, 2021. Full Changelog : https://github.com/BaptisteVandecrux/FirnCoVer/commits/1.0